Industrial electronics [technology 1999 analysis and forecast]. - Kaplan, G. (IEEE spectrum)
In old markets and new, power electronics, robots, intelligent control, and connectivity are becoming the pillars of industrial electronics and factory automation. Consider the integrated gate-commutated thyristor (IGCT). In the 18 months since its introduction by a Wisconsin company, motor drives based on the thyristor are already making a dent in the market for medium voltage and power levels-up to 6.6 kV and 10 MW-not least because other devices operate at similar power levels but higher losses. In the control and connectivity fields, open systems are vigorously pursued. Software and hardware advances in Java language technology are allowing manufacturers to break through the restrictions of proprietary systems and test real-time factory automation over the Internet, involving text, numerical data, and graphics. Open networking for the factory is strongly advocated by such industry leaders as Hirschmann Network Systems, in Riverdale, NJ and on printed-circuit boards, the use of vias under 150 μm in diameter (microvias) is taking hold, as packaging concepts like ball grid arrays cause component leads to shrink